The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/hepr.12579
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in stump pressure and assessment of images obtained from cone‐beam computed tomography during balloon‐occluded transarterial chemoembolization

Abstract: found in 8 patients. Arterial blood pressure was measured before, immediately after, and 5 minutes after balloon occlusion prior to intra-arterial injection, as well as before and after balloon deflation after intra-arterial injection. Images were assessed qualitatively by 2 radiologists as well as quantitatively by calculating the contrast-to-noise ratio.Results: We found no significant difference in pressure between immediately after and 5 minutes after balloon occlusion. Mean stump pressure before balloon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The interconnections or the absence of interconnections between DV branches create a wide range of possible collaterality-related values for BOASP. For example, for the case illustrated in Figure 8, the BOASP could take a value between 43 and 71 mmHg, which are between the values reported by Kakuta et al 31 The BOASP is also very much dependent on the vascular anatomy. In addition to the main branches of the HA such as PHA, RHA, and LHA, there are extrahepatic and intrahepatic arterial connections or collateral arteries that enable the liver tissue be fed even if a main branch is occluded.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The interconnections or the absence of interconnections between DV branches create a wide range of possible collaterality-related values for BOASP. For example, for the case illustrated in Figure 8, the BOASP could take a value between 43 and 71 mmHg, which are between the values reported by Kakuta et al 31 The BOASP is also very much dependent on the vascular anatomy. In addition to the main branches of the HA such as PHA, RHA, and LHA, there are extrahepatic and intrahepatic arterial connections or collateral arteries that enable the liver tissue be fed even if a main branch is occluded.…”
Section: Discussionsupporting
confidence: 67%
“…They reported that a dense accumulation of lipiodol emulsion occurred with a BOASP value below 64 mmHg. Likewise, Kakuta et al measured BOASP for 219 nodules in 27 patients at 5 temporal points: (i) before occlusion, (ii) immediately after occlusion, (iii) 5 minutes after occlusion, (iv) after intra‐arterial injection (before balloon deflation), and (v) after intra‐arterial injection (after balloon deflation). The pressures they measured were, on average, 97 mmHg at (i), 49.1 mmHg at (ii), 50.4 mmHg at (iii), 70.6 mmHg at (iv), and 96.5 mmHg at (v).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kakuta et al[ 29 ] examined the changes in the stump pressure with and without balloon occlusion as well as after B-TACE treatment. The mean blood pressure at the targeted occluded artery was 97 mmHg before balloon occlusion and decreased to 49.1 mmHg immediately after balloon occlusion, with a statistically significance[ 29 ]. Five minutes after balloon occlusion, the mean blood pressure was 50.4 mmHg, and the maintenance of a decreased blood pressure was observed[ 29 ].…”
Section: Mechanism Of B-tacementioning
confidence: 99%
“…Interestingly, the BOASP can be determined instantly and does not require a substantial duration of time to equilibrate for accurate assessment. 17 Intraprocedural image-based assessments of perfusion differ between B-TACE and c-TACE. While arterial perfusion typically correlates with the chemoembolic accumulation in cTACE, the arterial perfusion after balloon occlusion can be variable and does not always correlate with the final chemoembolic accumulation.…”
Section: B-tacementioning
confidence: 99%